Zambia : Report on Observance of Standards and Codes-Data Module, Response by the Authorities, and Detailed Assessments Using Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2005)
This report on the Observance of Standards and Codes data module provides an assessment of Zambia's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. Overall, the lack of effective coordination among all statistical producing agencies and users impedes the quality and transparency of statistics. In addition, no systematic program to assess users' needs is in place. All agencies have limited practices in informing the public of internal government access to statistics before wider data dissemination.